2003
DOI: 10.1680/macr.2003.55.5.471
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for determining the true specific fracture energy of concrete

Abstract: In a recent paper, Abdalla and Karihaloo confirmed the boundary effect hypothesis of Hu and Wittmann and observed that a size-independent specific fracture energy G F of concrete could be obtained by testing three point bend (TPB) or wedge splitting (WS) specimens containing either a very shallow or a deep starter notch. This observation was based on TPB and WS tests on limited number of specimens. In this paper, we have re-evaluated 26 test data sets on specific fracture energy of concrete published in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…Although these models are based on different fundamentals, they are related to each other. Cifuentes et al (2013) showed that if the size-dependent G f measured by the RILEM method is corrected according to the method of Elices and co-workers Guinea et al 1992;Planas et al 1992) or that of Hu and Wittmann (1992) (the latter admits a simplification as proposed by Karihaloo et al (2003) if the notch to depth ratios are well apart from each other), then the resulting specific fracture energy G F is very nearly the same and independent of the size of the specimen.…”
Section: Size Dependency Of the Specific Fracture Energy Of Concretementioning
confidence: 99%
“…Although these models are based on different fundamentals, they are related to each other. Cifuentes et al (2013) showed that if the size-dependent G f measured by the RILEM method is corrected according to the method of Elices and co-workers Guinea et al 1992;Planas et al 1992) or that of Hu and Wittmann (1992) (the latter admits a simplification as proposed by Karihaloo et al (2003) if the notch to depth ratios are well apart from each other), then the resulting specific fracture energy G F is very nearly the same and independent of the size of the specimen.…”
Section: Size Dependency Of the Specific Fracture Energy Of Concretementioning
confidence: 99%
“…50 for WS) identified for the determination of the true G F . 4 The optimised coefficients a 1 , a 2 and b 2 obtained by using the hinge model and minimising the difference between the theoretical and recorded load-CMOD curves are given in Table 2. The predictions from the hinge model corresponding to these parameters for each value of AE are compared with the mean experimental results in Figs 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have recently proposed a simple method for the determination of the true G F of a concrete mix that is independent of the shape and size of the test specimen. 3,4 This method requires the determination of the specific fracture energy G f (AE, W) on specimens of the same size W but one half of which contain a very shallow starter notch a (AE ¼ a/W) and the other half a deep starter notch. The two specific fracture energy values so determined depend on AE and W. The simplicity of the method lies in how the true specific fracture energy of the concrete mix G F can be calculated from the two size-dependent values G f (AE, W).…”
Section: Introductionmentioning
confidence: 99%
“…These F mechanisms cause the so-called tension softening of the material and can be particularly regarded as interpretation of the crack bending around aggregates, friction of cracks face and aggregate interlock, blinding of crack tip in pores, crack branching and others [1,3]. There were many attempts to capture/deal with the phenomena of the size/shape/boundary effect on fracture properties of quasi-brittle materials proposed with success in the last more than twenty years [5][6][7][8][9][10][11][12][13][14]; however, the applicability/validity of the suggested remedies are usually rather limited and not general. This is true also for the standardized work-of-fracture method for determination of fracture energy of concrete [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is true also for the standardized work-of-fracture method for determination of fracture energy of concrete [15]. The value of fracture energy determined by this method is strongly dependent on the specimen size and geometry [9,10,12] This phenomenon is caused by the change in the size and shape of the FPZ during crack propagation, from which the change of energy dissipated in this area results. This change is determined by the distance and the position of the crack tip and the FPZ in relation to free surfaces of the specimen [12].…”
Section: Introductionmentioning
confidence: 99%